The effect of instructional media NetSupport school on learning interest in office applications - Anggun Muliya Warni; Vevi Sunarti (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2025)
This study addressed low learning interest among participants in office application skills training at a community learning center by examining the use of NetSupport School as a digital instructional medium. A quantitative quasi-experimental design with a nonequivalent control group was employed, involving 40 participants divided into an experimental group and a control group. Learning interest was operationalized through enjoyment, attention, and active involvement, and measured using a validated questionnaire supported by observation data. The experimental group received instruction using NetSupport School for four sessions, while the control group followed conventional instruction. Data were analyzed using paired and independent sample t-tests. The results indicated a statistically significant increase in learning interest in the experimental group, whereas no significant change was observed in the control group. These findings suggest that digital classroom management tools can enhance learning interest in nonformal vocational training, although the results should be interpreted within the study’s contextual and methodological limitations.